2004
DOI: 10.1152/jn.00106.2003
|View full text |Cite
|
Sign up to set email alerts
|

Taurine Activates Strychnine-Sensitive Glycine Receptors in Neurons Freshly Isolated From Nucleus Accumbens of Young Rats

Abstract: . Although functional glycine receptors (GlyRs) are present in the mature nucleus accumbens (NAcc), an important area of the mesolimbic dopamine system involved in drug addiction, their role has been unclear because the NAcc contains little glycine. However, taurine, an agonist of GlyRs, is abundant throughout the brain, especially during early development. In the present study on freshly dissociated NAcc neurons from young Sprague-Dawley rats (12-to 21-day old), we found that both glycine and taurine can stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
29
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 64 publications
(56 reference statements)
4
29
0
Order By: Relevance
“…Although not directly comparable, the results of the present study are consistent with the results obtained by Jiang et al, namely, that taurine (300 µmol) binds primarily to the glycine receptor; however, at high concentrations, taurine (10 mmol) can also activate GABA A receptors in vitro [7] . In fact, Idrissi and Trenkner reported that taurine interacts directly with GABA A receptor in vitro [17] .…”
Section: Acta Pharmacologica Sinica Npgsupporting
confidence: 91%
See 1 more Smart Citation
“…Although not directly comparable, the results of the present study are consistent with the results obtained by Jiang et al, namely, that taurine (300 µmol) binds primarily to the glycine receptor; however, at high concentrations, taurine (10 mmol) can also activate GABA A receptors in vitro [7] . In fact, Idrissi and Trenkner reported that taurine interacts directly with GABA A receptor in vitro [17] .…”
Section: Acta Pharmacologica Sinica Npgsupporting
confidence: 91%
“…GABA and glycine are colocalized in interneurons in spinal laminae I-III [4,5] and are coreleased from the same interneurons [6] . However, taurine binds to glycine receptors in the CNS and functions as a partial agonist of GABA A receptors [7] , inhibiting behaviors evoked by intrathecal N-methyl-D-aspartate (NMDA) or kainate injection [8,9] . If GABA and glycine are coreleased from the same interneurons, and glycine-related amino acids act at GABA and glycine receptors to modulate low-threshold transmission via distinct but complementary mechanisms, then glycine or its related amino acids might inhibit bicuculline-induced allodynia.…”
mentioning
confidence: 99%
“…Taurine is a structural analog of the inhibitory neurotransmitters glycine and GABA, and activates both glycine and GABA A receptors. For example, low to moderate concentrations (200 M to 1 mM) of taurine have been shown to activate glycine receptors in the basolateral amygdala (McCool and Botting, 2000), hippocampus (Wu and Xu, 2003), nucleus accumbens (Jiang et al, 2004), supraoptic nucleus (Hussy et al, 1997), and inferior colliculus (Xu et al, 2004), whereas high concentrations of taurine (1-10 mM) activate GABA A receptors in these brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…The roles of endogenous taurine in the liver and heart are to increase bile acid secretion by forming bile acid conjugate [2] and regulate Ca 2+ kinetics to protect and improve the heart function [17], respectively. In the brain, taurine is also abundant, especially in the hippocampus, and modulates synaptic transmission as an inhibitory neuromodulator interacting with g-aminobutyric acid type A (GABA A ) or glycine receptors [9,22]. Recent electrophysiological studies using rat brain preparations, however, have shown that taurine application induced long-lasting synaptic potentiation [3,6].…”
mentioning
confidence: 99%